Autonomous motivation and self regulated learning: Determining factors of performance in snowboard and freeskiing - Sommer, M. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Snowboard and freeskiing seem to represents a somewhat different training-culture compared to `traditional` winter sports. Due to the absence of a typical coach utilizing customary coaching-strategies including provision of structure, instructions and feedback as tools for performance enhancement, these riders are required to take greater responsibility and control of their own learning processes. The aim of the present study was to investigate the existence of self-regulated learning (SRL - e.g. Toering, et al., 2009) and autonomous motivation (AM) (Self-determination Theory; Ryan & Deci, 2002) within this culture, and how these variables relate to development and skill level. Methods Forty-three snowboarders and freeskiers aged 15-23 years (M = 17.5, SD = 1.8), completed two questionnaires related to motivation (Behavioural Regulation in Sport Questionnaire - BRSQ; Lonsdale, et al., 2008) and SRL (Self-regulated learning questionnaire - SRLQ; Toering et al., 2013) during the on-snow season. BRSQ was distributed at the beginning (T1), mid (T2) and at the end of the season (T3). SRLQ was distributed at T2 and T3. The riders` current skill level, and seasonal development, which is a cumulative score of technical- (skill), tactical- (deliberateness), mental- (involvement) and physical (strength, agility) abilities, was rated by their coaches at T3. Results AM at T1, T2 and T3 was found to positively correlate with SRL at T3. Both SRL at T2 and T3 correlated positively with skill level. Regression analyzes indicate that AM at T1 may predict coach-rated development (B = 0.65, p = 0.03, R2 = 0.12), but not skill level. In turn, SRL at T2 was found to have a positive effect on skill level (B = 1.15, p = 0.05, R2 = 0.14), but not coach-rated development. Discussion Snowboarders and freeskiers display a high degree of AM, and in large part self-regulate their learning and development. Although not explicitly identified in the present study, the positive relation between AM and SRL, in combination with the separate effects of AM and SRL on development and skill level, indicate that SRL function as a mediating variable between motivation and skill level. The present results signify the importance of a training environment that facilitates autonomy and self-regulation in these sports.